Compact Wideband Circularly Polarized Dipole Antenna Using Modified Quadrature Hybrid Couplers - Wang, Heesu; Park, Ikmo (IEEE Transactions on Antennas and Propagation, 2021)
In this communication, we propose a novel circularly polarized (CP) dipole antenna fed by modified quadrature hybrid couplers (QHCs). In a conventional CP antenna, such as a sequentially rotated structure, the electrical length of the line connecting the radiating elements changes as the frequency changes. This characteristic produces a narrow axial ratio (AR) bandwidth and changes the radiation patterns of the array antenna at different frequencies. A modified QHC with minimal variation in the phase and amplitude difference between the output ports over a wide frequency range is used to achieve wide AR bandwidth and stable radiation patterns. The -10 dB impedance bandwidth of the proposed antenna is 4.1-7.6 GHz (58.3%), and the 3 dB AR bandwidth is 4.8-7.4 GHz (43.3%). The maximum gain is 4.4 dBic, and the 3 dB gain bandwidth is 5-7.5 GHz (40%). The antenna size is 21× 21×0.2032 mm3 (0.42× 0.42× 0.004λ {o}{3} at 6 GHz).
Keywords: Amplitude difference; Circularly polarized; Different frequency; Frequency changes; Impedance bandwidths; Quadrature hybrid couplers; Radiating elements; Wide frequency range; Circularly polarized (CP) antenna; dipole antenna; printed dipole; quadrature hybrid coupler (QHC); wideband antenna